PENGARUH INTENSITAS CAHAYA TERHADAP PERTUMBUHAN DAN PERKEMBANGAN TANAMAN KACANG MERAH - R. Siti Mustika Ningsih (Agroswagati Jurnal Agronomi, 2019)
Red beans (Phaseolus vulgaris) is the plant that classified to the tribe papilionaceae or legums. Red beans is legume crop commodity which a lot of Indonesian people like. That process of red beans growth occur through three steps, that is germination, primary and secondary growth. Germination marked by the appearance of radicles or plumula from inside the seeds. Red beans germination marked by cotyledon removal and plumula to the ground. Elongation of red beans occur in hypocotyl. The next process is primary growth that occur the embryo growth, stem ends and root tips. The last step is secondary growth, this step is the activity of cambium that forming secondary xylem and phloem. This red beans growth can’t separate from various factors that influence one of factors that influential is light. Light is influential factor that plant needs for do photosynthesis. In the plant the more light obtained will cause obstruction growth from the plant because the light will broke the work of growth hormone (auxin). So, plant that get a good light have shorter stems than plant that doesn’t get light.